Lysosomal gene ATP6AP1 promotes doxorubicin resistance via up-regulating autophagic flux in breast cancer - Yinjiao Fei; Xueqin Yan; Mingxing Liang; Shu Zhou; Di Xu; Lei Li; Weilin Xu; Yuxin Song; Zhen Zhu; Jian Zhang (Cancer Cell International)
Abstract Background Breast cancer remains the most prevalent malignancy in women. Chemotherapy is the primary systemic treatment modality, and the effectiveness of treatment is often hampered by chemoresistance. Autophagy has been implicated in promoting chemoresistance, as elevated autophagic flux supports tumor cell survival under therapeutic stress. Since lysosomes are essential for the completion of autophagy, their role in autophagy-related chemoresistance has been insufficiently studied. This study aims to elucidate the role of the lysosomal gene ATP6AP1 in promoting chemoresistance in breast cancer by upregulating autophagic flux. Methods Doxorubicin-induced cell death was assessed by cytotoxicity, flow cytometry, lactate dehydrogenase (LDH) release assays in various breast cancer cell lines. Autophagic flux was assessed with western blot and the mRFP-GFP-LC3 fluorescence imaging. Breast cancer cells were infected with shRNA lentivirus targeting ATP6AP1, allowing investigation its tole in doxorubicin-induced cell death. ATP6AP1 expression and its association with prognosis were evaluated using public databases and immunohistochemistry. Results Doxorubicin-induced cell death in breast cancer cells is negatively correlated with increased autophagic flux and lysosomal acidification. The lysosomal gene ATP6AP1, which plays a role in autophagic processes, is upregulated in breast cancer tissues. Knocking down ATP6AP1 reduces autophagy-mediated doxorubicin resistance by inhibiting autophagic flux and lysosomal acidification in breast cancer cells. Data analysis from public databases and our cohort indicate that elevated ATP6AP1 expression correlates with poor response to doxorubicin-based neoadjuvant chemotherapy (NAC) and worse prognosis. Conclusions Doxorubicin-induced cytotoxicity is associated with autophagy flux in breast cancer. The lysosomal gene ATP6AP1 facilitates autolysosome acidification and contributes to doxorubicin resistance in breast cancer.